LARGE VERSUS SMALL CLASSES IN ELEMENTARY ACCOUNTING. - Schattke, Rudy; McAllister, LeRay (The Accounting Review, 1962)
In discussions of techniques of communicating accounting knowledge, one subject that frequently arises is the question of the optimizing size of classes. Some feel that small classes are the only means of effectively teaching accounting. Others feel that large classes can be just as effectual, and are considerably less expensive. The question is certainly an interesting one, and it is one which deserves study in these times of rapidly increasing enrollments. As might be expected, a vast majority of both teachers and students exhibited a preference for small elementary accounting classes. A considerable number of teachers could be effective under certain conditions, even though they would not be as effective as small classes. Those schools which had experience with large classes were generally more optimistic about them than those who had no experience. Both personal experience and questionnaire inquiries of teachers and students indicate that small classes are preferable to large ones from a pedagogical standpoint. Thus, given adequate financial resources and adequate staff, the decision between the two is obvious. In the absence of either of these conditions, there are some indications that large classes may be effectual means of teaching accounting if there are good physical facilities, full use of visual aids and laboratories of about 25 students where individual attention may be received.